Effects of hydropeaking on the attached eggs of a rheophilic cyprinid species - Bartoň, Daniel (Jihočeská univerzita, 2019)
Effects of artificial water fluctuations called hydropeaking on the detachment rates of adhesive eggs were studied using a rheophlic fish (asp Leuciscus aspius) as a model species. I attempted to relate egg density to abiotic conditions of the spawning ground and identify optimal conditions for the eggs. Egg densities were also studied during spawning season when hydropeaking occurred. In the experimental setup, egg detachment rates were tested with different speeds, substrate type and exposition time and critical conditions for the eggs were assessed.
Effects of hydropeaking on the attached eggs of a rheophilic cyprinid species
Keywords: fish reproduction; hatching; wildlife conservation; river ecology; mortality; fish reproduction; hatching; wildlife conservation; river ecology; mortality